1947
DOI: 10.1172/jci101870
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Local Cooling on the Filtration and Absorption of Fluid in the Human Forearm

Abstract: Studies relating to the effects of cold on the permeability of human capillaries to protein and fluid have assumed practical importance in recent years because of current interest in refrigeration anesthesia and cryotherapy, as well as because of the casualties caused by exposure to cold during the recent war. Clinical (1) and experimental (2, 3) studies have shown that true frostbite increases the permeability of the capillary wall to both protein and fluid, but less is known quantitatively concerning the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1957
1957
1981
1981

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
0
8
1
Order By: Relevance
“…Krogh et al (16) used the pressure plethysmograph to circumvent this objection; it theoretically determines the volume of the segment after collapse of all vascular components. Although a counterpressure of 55 cm water was at first thought to be sufficient to empty the vessels in a limb in which arterial inflow had been stopped, Landis and Gibbon (17) and Brown et al (1) found it necessary to increase counterpressure to 200 mm Hg. The technique has proved to be relatively satisfactory and has provided consistent and useful data (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Krogh et al (16) used the pressure plethysmograph to circumvent this objection; it theoretically determines the volume of the segment after collapse of all vascular components. Although a counterpressure of 55 cm water was at first thought to be sufficient to empty the vessels in a limb in which arterial inflow had been stopped, Landis and Gibbon (17) and Brown et al (1) found it necessary to increase counterpressure to 200 mm Hg. The technique has proved to be relatively satisfactory and has provided consistent and useful data (18).…”
Section: Discussionmentioning
confidence: 99%
“…1, upper diagram) are interconnected and applied around the part, with arrangements to assure connection of the lower strips to the skin. 1 For each calibration, the upper set of copper strips is short circuited to the same potential; this effectively moves the charges iThe materials from which this calibrating system was built were generously supplied by the Remco Tape Products Company of North Hollywood, California. from a corresponding area of skin through 1 mm to the upper level.…”
Section: Charge Displacement Calibration System Copper Strips (Hatchmentioning
confidence: 99%
See 1 more Smart Citation
“…After three or four measurements, however, the decrease in each measurement became constant, ranging from 0 5 to 1-5 ml. This amount gave the volume of interstitial fluid which was pressed out of the calf due to the com-732 TRANSCAPILLARY FLUID MOVEMENT pression during each measurement (Brown, Wise & Wheeler, 1947;Landis & Pappenheimer, 1964). This volume was obtained in each subject and used for the correction, as adopted by Brown et al (1947), to evaluate the actual change in reduced calf volume due to the ingestion of hypertonic saline.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that protein-poor fluid moves from the vascular to the extravascular space during venous congestion of the forearm or lower extremity (1)(2)(3)(4)(5) and during a more generalized increase of venous pressure such as is induced by quiet standing (6,7) or by pressure breathing (8,9). No quantitative comparison has been made, however, between local and generalized congestion as to the quantity and duration of capillary filtration per unit increase of venous pressure.…”
mentioning
confidence: 99%